Bridging Oral Pathology with Diagnostics by Comparative Analysis of Oral Fibrosis as a Precursor to Carcinogenesis: A Systematic Review and Meta-Analysis - Tayyaba Rafiq; Anum Usman; Madeeha Minhas; Sajid Ali Majeedano; Aliya Zaman; Shahzaman Memon (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Oral Submucous Fibrosis (OSF) is a chronic, potentially malignant condition that causes progressive fibrosis of the oral mucosa because people consume areca nuts. The purpose of this systematic review and meta-analysis was to compile the most recent data on molecular changes in OSF and assess how they relate to malignant transformation.